Heterogeneous impact of artificial intelligence on carbon emission intensity: Empirical test based on provincial panel data in China - Du, Meng; Zhang, Yifan; Dong, Hai; Zhou, Xiangjun (Frontiers in Ecology and Evolution, 2023)
Energy conservation and emission reduction, as a major policy of China for a long time, has been put on the key strategic position. Based on the panel data of 30 provinces, cities and districts in China from 2006 to 2019, this paper uses fixed effect model and spatial Durbin model to explore the effect and mechanism of artificial intelligence (AI) on regional carbon emission intensity (CEI). The results show that: (1) there is a significant inverted U-shaped between AI and CEI, that is, with the deepening of the development of AI, CEI first increases and then decreases. (2) There is a significant spatial correlation between the development of AI and CEI in China. (3) AI has a significant spatial spillover effect on CEI of adjacent regions, and it shows an inverted U-shaped track-from promoting to restraining. The conclusion provides policy implications for the formulation of AI development strategy and so on during the specific period.